2018
DOI: 10.21053/ceo.2017.00493
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin Induces MUC5AC Expression via Activation of NF-κB in Human Airway Epithelial Cells

Abstract: Objectives Clusterin (CLU) is known as apolipoprotein J, and has three isoforms with different biological functions. CLU is associated with various diseases such as Alzheimer disease, atherosclerosis, and some malignancies. Recent studies report an association of CLU with inflammation and immune response in inflammatory airway diseases. However, the effect of CLU on mucin secretion of airway epithelial cells has not yet been understood. Therefore, the effect and brief signaling pathway of CLU on MUC5AC (as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Sol and colleagues have reported that the levels of sputum CLU were significantly lower in asthmatic patients than healthy controls, and moreover, the levels of CLU were associated with asthma severity [ 41 ]. Another study has indicated that CLU was associated with mucus secretion in human airway epithelial cells via activation of NF- κ B [ 42 ]. The present study has indicated a relationship between CLU and CRSwNP, with significantly decreased CLU level in CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
“…Sol and colleagues have reported that the levels of sputum CLU were significantly lower in asthmatic patients than healthy controls, and moreover, the levels of CLU were associated with asthma severity [ 41 ]. Another study has indicated that CLU was associated with mucus secretion in human airway epithelial cells via activation of NF- κ B [ 42 ]. The present study has indicated a relationship between CLU and CRSwNP, with significantly decreased CLU level in CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
“…Using comparative microarray profiling, they further indicated that there is a positive correlation between the level of secretory CLU and the expression of many NFκB‐regulated genes. Furthermore, several other groups have also found evidence that CLU increases NFκB activity in various cell types including macrophages, endometrial cancer cells, pancreatic cancer cells, and airway epithelial cells 44‐47 . The factors underlying these conflicting inhibitory and stimulatory effects of CLU on IκB degradation have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several other groups have also found evidence that CLU increases NFκB activity in various cell types including macrophages, endometrial cancer cells, pancreatic cancer cells, and airway epithelial cells. [44][45][46][47] The factors underlying these conflicting inhibitory and stimulatory effects of CLU on IκB degradation have yet to be elucidated. Interestingly, CLU-mediated inhibition of IκB degradation has been reported in cells of other tissues including neuroblastoma cells, synoviocytes, kidney tubular epithelial cells, cardiocytes, and HeLa cells, none of which is in keeping with the tissues that exhibit increased IκB degradation.…”
Section: F I G U R Ementioning
confidence: 99%
“…The slides were counterstained with hematoxylin and mounted. 14 PAS staining was performed using the PAS staining kit (Merck Millipore, Darmstadt, Germany) according to the manufacturer's protocol. Immunohistochemistry and PAS staining of MUC5AC was analyzed on three different sections in five tissues per group and classified by two independent blinded observers using a semi-quantitative method.…”
Section: Immunohistochemistry (Ihc) and Periodic-acid-schiff (Pas) Stmentioning
confidence: 99%